DETERMINANTS OF UNDERGRADUATE STUDENTS ACADEMIC PERFORMANCE IN UITM KOTA BHARU - Amirah Nasuha Zuki,; Siti Nur Zahirah Omar,; Nor Ayuni Balkhis Syarul Azri,; Nur Shazliyana Zuladnan,; Nur Adlin Sofiya Ahmad Mokhjailani, (Journal of Islamic, Social, Economics and Development, 2024)
This study aims to investigate how family involvement, stress levels, learning environment, and self-efficacy can influence the academic achievement of a large group of students. The total population of students included in this study was 1,227, with a sample size of 291 undergraduate students from UiTM Kota Bharu. The findings of this study reveal that family involvement has a high positive correlation with academic achievement with r = 0.764 that family involvement has the strongest contribution to academic achievement. Not only that, through regression analysis, with r² = 0.583 and adjusted r² = 0.582, that illustrates 58.2% of family involvement has influenced the academic achievement of the undergraduate students in UiTM Kota Bharu while another 41.8% is influenced by another factor. Meanwhile, other factors including stress, learning environment, and self-efficacy have shown a moderate positive correlation towards academic achievement.